(3GdfRgI GdeHgLI, aj JTMjP GdCPgGf hJYOjd GdCeRLIs - (3GdCfWGcj, GdHUjQ (B- (3GdWHjH, OGhO Hf YeQ, (B1008 (3g`s ((3Ydj OQGOGQs)
(3ChdgG (B:s
(3adeG cGf JfGaS GdfahS GdcGedI hZGjI eQei eQGe GdYbhd GdaGVdI eG Hg GdNdGU ef bjhO GdTghGJ hZGjJg GdCHOj ef LRjd GdSYGOGJ hLH Ydi ef GSJMUd TQGFW GdEfJGL hGdbjGS s
(3BNQgG (B:s
(3hcPG MH TLQI eQje cd hGMOI HSfI gPG BNQ eG CQOfG JdNjUg eeG MQQ aj gPG GdTCf MSH GdEecGf eG GbJVGg GdMGd hGdReGf hef CQGO RjGOI aYdjg HJPcQJfG Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\333s
(3cTa GdXfhf (B1\307s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs